Interactive Effects of Potassium and Mycorrhizal Fungi on Glomalin and Biochemical Responses of Sunflower Grown in a Pb and Zn Contaminated Soil. Issue 4 (19th May 2022) - Jahantigh, Mojtaba; Ahmadabadi, Zahra; Motesharezadeh, Babak; Alikhani, Hossein Ali; Hosseini, Seyedeh Mahsa; Ma, Qifu
ABSTRACT: It is well documented that sole application of potassium (K) or mycorrhizal fungi can alleviate heavy metal stress in plants. As an indicator of the efficient defense in the mycorrhizal fungi-plant system, glomalin synthesis in the rhizosphere can be determined. In this study, interactive effects of mycorrhizal fungi (MY) and K on glomalin content, heavy metal uptake and mycorrhizal properties of sunflower plants were examined with three soil K levels (0, 100, and 200 mg K kg −1 using K2 SO4 ). The three levels of mycorrhization are: i) no mycorrhizal inoculation, ii) Rhizophagus irregularis inoculation, and iii) mixed mycorrhizal inoculum application. Joint application of potassium and mycorrhiza significantly increased the percentage of root colonization and easily extractable glomalin (EEG), showing 56% root colonization in the treatment of K100 + mixed mycorrhiza and 178 µg EEG g −1 in the treatment of K200 + mixed mycorrhiza. Joint application of MY and K significantly reduced the translocation of heavy metals to the shoot of the plants. The highest total uptake of Zn by plants per pot (2.01 mg pot −1 ) and Pb (0.78 mg pot −1 ) were found in non-mycorrhizal plants. The MY and K treatments also increased the chlorophyll content and leaf area index by 57%. This study concluded that application of potassium and mycorrhizal fungi enhanced glomalin production and increased plant resistance to heavy metal stress.